2004
DOI: 10.1073/pnas.0401882101
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-timetable methods for detection of body time and rhythm disorders from single-time-point genome-wide expression profiles

Abstract: Detection of individual body time (BT) via a single-time-point assay has been a longstanding unfulfilled dream in medicine, because BT information can be exploited to maximize potency and minimize toxicity during drug administration and thus will enable highly optimized medication. To achieve this dream, we created a ''molecular timetable'' composed of >100 ''time-indicating genes,'' whose gene expression levels can represent internal BT. Here we describe a robust method called the ''molecular-timetable method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
136
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 28 publications
0
136
0
Order By: Relevance
“…Identification of the circadian-oscillating metabolites is important for connecting our current metabolite timetable of human blood to previously reported circadian biology in humans. Identification is also important for further development of our method because once a metabolite is identified, we can update the circadianmetabolite reference list in our human blood timetable, which will improve the sensitivity and specificity of the molecular timetable (12,42). Therefore, we attempted to identify several circadian-oscillating metabolites in constructing our metabolite timetable and found that a large fraction belong to the steroid hormone metabolism pathway (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Identification of the circadian-oscillating metabolites is important for connecting our current metabolite timetable of human blood to previously reported circadian biology in humans. Identification is also important for further development of our method because once a metabolite is identified, we can update the circadianmetabolite reference list in our human blood timetable, which will improve the sensitivity and specificity of the molecular timetable (12,42). Therefore, we attempted to identify several circadian-oscillating metabolites in constructing our metabolite timetable and found that a large fraction belong to the steroid hormone metabolism pathway (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We note that a molecular timetable concept can be applied not only for circadian-oscillating metabolites, but also for other circadian-oscillating substances (12,42) and in other tissues like human hair follicle cells from the head or chin (63). Comparing molecular timetable methods with different reference molecules such as clock-controlled RNAs in humans will be of interest to reveal internal synchronization (or desynchronization) between different peripheral clocks such as blood clocks and skin clocks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We moreover succeeded in single-point phase prediction using expression data for nine clock genes obtained from mouse peripheral tissues; this suggests that even one-point phase prediction may be possible for human data with our standard-curve method, using more genes whose rhythms of expression are consistently detectable. There is a report on a single-point phase prediction method using expression profiles of more than 100 circadian output genes in mouse liver (23).…”
Section: Correlation Between Human Behavioral Rhythms and Circadian Cmentioning
confidence: 99%